Development of in situ pcr technique for detection of velogenic newcastle disease virus strain - Elawad, H. A.; Bejo, Mohd Hair; Omar, Abdul Rahman; Arshad, Siti Suri; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)

(untitled)
A velogenic Newcastle disease virus (vNDV) strain (AF2240) was inoculated intranasally in 3-week-old specific pathogen free (SPF) chickens. Control was included and these chickens were not inoculated with the virus. The chickens were sacrificed at various intervals and samples of brain, caecal tonsils, liver, spleen, and trachea were fixed in 10% buffered formalin, processed and embedded in wax. A digoxigenin-labeled probe was designed according to the sequence of fusion gene (vNDV). By application of in situ PCR technique, the probe was evaluated as a marker of the gene and to subsequently detect the presence of the virus. The technique was carried out on tissues of chickens collected at 3, 6, and 7 days post inoculation (pi). The virus was detected in all of the tissues at days 3, 6 and 7 pi. The virus was not detected in the control group. It was concluded that this study has successfully developed an in situ PCR technique for detection of vNDV by formation of specific probes complementary to the fusion gene.